Southern Highbush Blueberry Cultivars from the University of Florida: HS1245, rev. 9/2022 - Phillips, Doug; Williamson, Jeffrey; Lyrene, Paul; Munoz, Patricio (EDIS, 2022)
This publication provides historical background on southern highbush blueberries (SHB), and information on specific UF/IFAS cultivars that can be a helpful resource for SHB growers. Written by D. A. Phillips, J. G. Williamson, P. M. Lyrene, and P. R. Munoz, and published by the UF/IFAS Horticultural Sciences Department, revised September 2022.